Thermal ion imagers and Langmuir probes in the Swarm electric field instruments - Knudsen, D. J.; Burchill, J. K.; Buchert, S. C.; Eriksson, A. I.; Gill, R.; Wahlund, J.‐E.; Åhlen, L.; Smith, M.; Moffat, B. (Journal of geophysical research. Space physics, 2017)
The European Space Agency's three Swarm satellites were launched on 22 November 2013 into nearly polar, circular orbits, eventually reaching altitudes of 460 km (Swarm A and C) and 510 km (Swarm B). Swarm's multiyear mission is to make precision, multipoint measurements of low‐frequency magnetic and electric fields in Earth's ionosphere for the purpose of characterizing magnetic fields generated both inside and external to the Earth, along with the electric fields and other plasma parameters associated with electric current systems in the ionosphere and magnetosphere. Electric fields perpendicular to the magnetic field B→ are determined through ion drift velocity v→i and magnetic field measurements via the relation E→⊥=−v→i×B→. Ion drift is derived from two‐dimensional images of low‐energy ion distribution functions provided by two Thermal Ion Imager (TII) sensors viewing in the horizontal and vertical planes; v→i is corrected for spacecraft potential as determined by two Langmuir probes (LPs) which also measure plasma density ne and electron temperature Te. The TII sensors use a microchannel‐plate‐intensified phosphor screen imaged by a charge‐coupled device to generate high‐resolution distribution images (66 × 40 pixels) at a rate of 16 s−1. Images are partially processed on board and further on the ground to generate calibrated data products at a rate of 2 s−1; these include v→i, E→⊥, and ion temperature Ti in addition to electron temperature Te and plasma density ne from the LPs. Key Points Swarm TII sensors provide ion velocity and temperature from core ion distribution function images CCD‐based imaging detectors in the TIIs support event rates that are much higher than possible with charge amplifier‐based systems Swarm LPs use a harmonic‐mode technique to obtain electron density, temperature, and spacecraft potential at high rates